The influence of system’s interactions on halal business performance in small-medium enterprises food manufacturers - Nainatul Farzuha, Nor (2023)
Halal products are becoming more popular worldwide, including in Malaysia. Recent trends emphasize halal business performance in small-medium food Manufacturers. The purpose of this study is to examine the system's interactions That consisted of machine, people, and knowledge management and small-medium Enterprises (SME) halal business performance in Malaysia. The underpinning Theory used in this study was System Theory which highlighted the importance of The interactions of the key variables i.e. Machine, people, and knowledge Management on the outcome of the business. Hence, the System Theory Underpinned the research framework. The environment served as a mediator Between the key variables and halal business performance. Data were collected From respondents among the top management who represented smes halal food Manufacturers. Thus, the unit analysis in this study was the top management who Consisted of mainly the owner and the Chief Executive Officer of the company. The Partial Least Squares Structural Equation Modeling (PLS-SEM) main steps Were conducted accordingly when used for the data analyses. The key findings Showed machine and knowledge management were significantly related to halal Business performance. In addition to that, the environment mediated the Relationship between machine, people, and knowledge management towards halal Business performance. This study hoped to contribute to an increased Understanding of the systems’ interactions in SME halal food manufacturers for Business performance enhancement. It could contribute to the body of knowledge In business performance studies particularly on strategic management’s research Interest. The implications for practice in terms of offering the industry players to Focus focusing on the key components system to enhance halal business Performance